Optimization of Process Parameters for Controlled Ring-Opening Polymerization of Lactide to Produce Poly(L-Lactide) Diols as Precursor for Polyurethanes. (21st November 2016) - Monga, Sheetal; Kaushik, Anupama; Gupta, Bhuvanesh
ABSTRACT: Series of poly(L -Lactide) diols with molecular weights ( M n ) in 2, 069–4, 811 g mol −1 were synthesized fromL -Lactide using stannous octoate catalyst and 1, 4-butanediol chain extender. Operating conditions, i.e., temperature, catalyst concentration, chain extender concentration, and reaction time, were optimized. Maximum monomer conversion and M n were observed at 0.5 mol% SnOct2 and 1.0 mol% 1, 4 butanediol (BDO) at 145°C. Poly(L -Lactide) diols were analyzed by Fourier transform infrared, proton nuclear magnetic resonance, end-group analysis, and X-ray diffraction techniques. Fourier transform infrared confirmed the formation of poly(L -Lactide) diols. Poly(L -Lactide) diols' % degree of crystallinity was determined by X-ray diffraction. M n was calculated by proton nuclear magnetic resonance and end-group analysis. GRAPHICAL ABSTRACT: